Thanatosis in the Gold-striped Frog Lithodytes lineatus (Anura: Leptodactylidae) in the tropical dry forest of northeastern Colombia - Díaz, Giovany (2025)
Predation forces prey to develop multiple forms of evasion, including thanatosis, as a behavior that leads to the adoption of a posture where the animal appears to be dead. In this study we report for the first time thanatosis as a strategy present in the genus Lithodytes and the species L. lineatus, adding one more behavior to a list that includes Batesian mimicry, Müllerian mimicry, deimatic behavior and chemical mimicry.